Electrochemical assessment of laser-treated titanium alloy used for dental applications at acidic pH condition (in vitro study) - Dalia Ahmed Abd El Daym; Mostafa Esam Gheith; Nadia Ahmed Abbas; Laila Ahmed Rashed; Zeinab A Abd El Aziz (Wolters Kluwer Medknow Publications, 2019)
Background: Titanium alloys are widely used in dental applications as they have good mechanical and biological properties. Implant failure is more likely to occur in inflammatory diseases related to acidic pH. The aim of the present study was to assess the effect of erbium chromium-doped yttrium-scandium-gallium-garnet 2780 nm laser surface treatment on the electrochemical behavior of titanium alloy (Ti-6Al-4V) at acidic pH. Materials and Methods: In this in vitro study, a total of 20 discs of titanium alloy (Ti-6Al-4V) were used. First group, ten discs were irradiated with Er, Cr: YSGG laser which was operating in a normal room atmosphere and temperature at power 2W for 20 s at a constant distance of 0.5-1 mm with the laser system. The second group, ten discs untreated. The electrochemical behavior for both groups was investigated in simulated body fluid at pH 5.20 for up to 864 h at 192, 360, 696, and 864 h intervals using potentiodynamic polarization test and electrochemical impedance spectroscopy to evaluate the corrosion resistance. Results: Laser-treated Ti-6Al-4V showed higher corrosion resistance at pH 5.20 compared to the untreated alloy. Immersion time affected the electrochemical behavior. Conclusion: Er, Cr: YSGG laser could improve the corrosion resistance of Ti-6Al-4V at acidic pH.